Pre-term spontaneous uterine rupture in an unscarred uterus: a case report - Fatima, Maryam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine rupture is a life-threatening obstetrical emergency that needs prompt diagnosis and management. One of its leading risk factors is previous uterine surgical intervention like c-section or myomectomy. Most of these cases have predisposing factors, like trial of labour, prolonged neglected labour and injudicious augmentation/induction of labour. The risk of uterine rupture, in a pregnant unscarred uterus primarily without labour, is extremely rare. We present a case of spontaneous uterine rupture at 29+6 weeks. The patient was multigravida and presented with PPROM, followed by moderate APH and sudden onset of abdominal pain. There was no history of previous uterine surgery or any evidence of onset of labour. Her observations were normal. The CTG was showing deceleration. Category 1 c-section was done in view of placental abruption. Intraoperatively, midline rupture was diagnosed. The baby was born with good APGAR score. The postoperative recovery was smooth, and the patient was discharged after counselling on subsequent pregnancy. Obstetrician should keep a high index of suspicion of uterine rupture, in women with APH and abdominal tenderness, alongside the differential diagnosis of placental abruption.